Production Of Tannase By Aspergillus Niger Using Mangrove (Rhizophora Apiculata) Bark Under Solid Substrate Fermentation. - Tan , Wee Yee (2010)

(untitled)
Rhizophora apiculata bark is tannin rich waste material from charcoal industry, and was utilized as the solid substrate for the production of tannase in solid substrate fermentation system. Upon improvement of physical and chemical parameters via a simple shake flask system, combination of 0.75 mm and 2.00 mm of substrate particles, Czapek-Dox medium (pH7) as moisturizing agent, initial moisture content of 1:1.5 (w/v), incubation temperature at 30°C, mixing at every 24 hours and inoculum size of 1 × 106 spores/ml showed tannase achieved 4.97 U/g of fermented substrate on the 6th day of cultivation time. After supplementation of 5% (w/w) tannic acid and 1% (w/w) of urea, tannase achieved 39.34 U/g of fermented substrate after 6 days of cultivation.